Anti-cancer activity of midostaurin in hormone refractory human prostate cancer DU145 cells - Sun, Jin-Jun; Kan, Shi-Feng; Sun, Guan-Xing (Bangladesh Journal of Pharmacology, 2016)
We tried a new method of prostate cancer treatment by inducing in vitro differentiation which resulted in reduction of cancer cells growth. A protein kinase inhibitor, midostaurin's ability to trigger the human prostate cancer cell line, DU145 to segregate into nerve cells was studied. Midostaurin (100 nM) suppressed the growth of DU145 cells but without change in the number of dead cells. Midostaurin started to extend neurites on DU145 cells after 24 hours and differentiated into nerve cells by 72 hours. The microtubule was stabilized by tau protein and its mRNA expression showed time-dependent increase in midostaurin-treated DU145 cells. At the same time, the amount of acetylcholinesterase was also increased. The midostaurin-treated DU145 cells showed 40% less activity than control in the colony forming assay. The results suggests that midostaurin can induce differentiation of DU145 cells into nerve cells.